Defatted maize germ in equine diets - Camila Giunco; Gabriela Ribeiro; Liandra Maria Abaker Bertipaglia; Mikaele Alexandre Pereira; Olivia Carmen Araújo Nascimento; Roberta Ariboni Brandi (Bioscience Journal, 2016)
This study investigated the inclusion levels of defatted maize germ (DMG) in the diet of horses by determining the apparent digestibility coefficients of the nutrients, and the physicochemical parameters of feaces and blood samples. Four adult horses, weighing 483.3 ± 27.5 kg average, arranged in 4x4 Latin square were used. The energy provided by the diets came from hay, 50% (Jiggs hay), and from the concentrate, 50%, with increasing DMG levels (0, 10, 20 and 30%). Digestibility was determined using samples from total feaces collection. The characteristics of color, consistency, pH and buffering capacity (BC) 5 and 6 of the feaces were determined daily during the collection days. The blood samples were collected by venipuncture of the jugular, with vacuum tubes, to determine the concentration of glucose, triglycerides, cholesterol and insulin using biochemical kits and the concentration of short-chain fatty acids, by gas chromatography. The diets did not affect significantly (P> 0.05) the digestibility of nutrients, fecal pH (mean 6.7), buffering capacity at pH 5 (22.7) and pH 6 (6.9), and fecal concentration of short-chain fatty acids. Likewise, diets did not affect significantly (P> 0.05) the blood concentrations of glucose, insulin, cholesterol, and total short-chain fatty acids. However, diets changed significantly (P <0.05) the blood concentrations of triglycerides, described by the equation ŷ = 30.62 + 0.26x. The triglycerides, glucose and insulin variables also changed significantly (P <0.05) over time, according to the following equations: ŷ = 32.30 + 0.87x; ŷ = 85.93 + 3.17x - 0.61x²; and y = 3.19 + 1.38x - 0.22x², respectively. The defatted maize germ can be included up to 30% of the concentrate (up to 9.6% of the diet) without changing the diet apparent digestibility coefficient, and feaces and blood physicochemical parameters. This ingredient can be an alternative for high fiber diets and can contribute to formulating diets with lower glycemic and insulinemic indexes.